PERSPECTIVE DIRECTIONS OF PATRIOTIC EDUCATION - I. Ya. Murzina; S. V. Kazakova (Russian State Vocational Pedagogical University, 2019)
Introduction. Nowadays, patriotic education is a strategic reference point of the Russian education system. However, in the modern sociocultural situation, characterised by diversity, discrepancy, multi-vector nature of development of society and polystylicity of culture, it is necessary to revise the forms of patriotic education in order to adjust them in accordance with the  requirements and mental features of new young generation - so-called generation Z, which is considerably different from the previous generation of peers.The aims of the research were the following: to identify promising areas and vectors of patriotic education, to demonstrate its resources and to highlight the most relevant means and possibilities, which are appropriate to present-day realities.Methodology and research methods. The work was based on the method of discursive analysis, which allows the dependence of patriotic education practices on modern realities and socio-psychological characteristics of adolescents and youth to be revealed. In the course of the research, the methods of comparative analysis, systematisation and classification were employed. Results and scientific novelty. The conceptual and category-based framework of patriotic education and its structure are specified. Patriotism is considered as the most important component of the value-normative system of a personality. Patriotism is based on a positive cultural identity. Patriotism is distinguished by an active character-readiness and ability of a person to transform his or her  feelings towards homeland into deeds and acts, which are necessary for the good of the country. The analysis of practices of patriotic education in different countries allowed the authors to allocate two basic directions - civil-patriotic and military-patriotic education, which act as the complementary components of integral system. Civil-patriotic education is a purposeful, consciously carried out pedagogical process of organisation and management of learners' activities for mastering socio-cultural, socio-political, economic, moral and ethical experience of democratic relations through media education and participation in socially approved projects, civil-law campaigns and charitable events, which foster tolerance for various categories of fellow citizens. Military-patriotic education implies the formation of necessary qualities and skills for performance of a military duty in ranks of the Russian Federation's Armed Forces and, furthermore, for understanding and awareness of the personal role and place in service to the Fatherland. This direction involves education towards military traditions, museum pedagogics, participation in historical reconstructions and specially designed computer games related to military-patriotic issues.The list of educational practices, outlined in the present publication, does not purport to be complete and exhaustive. The task of authors consisted in the search for and choice of those, which, on the one hand, fill an ideological construct "patriotism" with live contents, attract teenagers and youth, and, on the other hand, answer the requests of society for education of a socially responsible personality with sustainable value system. Practical significance of the research is determined by the appropriateness and efficiency of applying the described forms and methods of educational work into teaching practice.